PENGARUH KOHESIVITAS KELOMPOK TERHADAP SIKAP KEWIRAUSAHAAN ANGGOTA MAJELIS TA’LIM KAMPUNG MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Rafi Gusnandi Putra; Titi Maemunaty; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of group cohesiveness on the entrepreneurial attitude of the members of the ta'lim council in Maredan Barat Village, Tualang District, Siak Regency. The formulation of the problem in this study is Is there a significant and positive influence of group cohesiveness on the entrepreneurial attitudes of members of Majelis Ta'lim in Maredan Barat Village, Tualang District, Siak Regency? This study consisted of 2 variables, namely the group cohesiveness variable (X) and the entrepreneurial attitude variable (Y), where the group cohesiveness variable (X) had 4 indicators and the entrepreneurial attitude variable (Y) had 6 indicators. The population in this writing is the members of the Majelis Ta'lim Kampung Maredan Barat, Tualang Siak District, as many as 344 members of the Majelis Ta'lim. The sampling technique with stratified random sampling used was proportionate stratified random sampling, which is a sampling technique in which the population has heterogeneous members or elements and has proportional stratification. The data collection technique in this study was a questionnaire technique, which amounted to 75 statements for the group cohesiveness variable (X) and 99 statements for the entrepreneurial attitude variable (Y). Data obtained from respondents, amounting to 20 people for the trial sample and 78 people for the research sample. After the questionnaire was tested, there were 17 invalid statements on the group cohesiveness variable and 28 invalid statements on the entrepreneurial attitude variable, and the researcher discarded invalid statements. Based on the descriptive analysis based on variables, it is obtained the level of entrepreneurial attitudes in the environment around the members of the ta'lim council with a mean magnitude of 4.29 which is at a very high interpretation.Based on descriptive analysis based on variables, the level of group cohesiveness in the environment around assembly members is obtained. ta'lim with a mean magnitude of 4.10 which is in the high interpretation. Obtained a significant influence between the group cohesiveness variable (X) on entrepreneurial attitudes (Y) Members of the Ta'lim Council in Maredan Barat Village, Tualang District, Siak Regency, the big influence is 27.1% with a high interpretation, because there are still 72.9% determined by other factors that are not part of this writing.Key Words: Group Cohesiveness, Entrepreneurial Attitude, Members Of The Ta'lim Assembly